Bat fauna of Mato Grosso do Sul, southwestern Brazil - Fischer, Erich; Santos, Carolina Ferreira; Carvalho, Luiz Felipe Alves da Cunha; Camargo, George; Cunha, Nicolay Leme da; Silveira, Maurício; Bordignon, Marcelo Oscar; Silva, Camila de Lima (Biota Neotropica, 2015)
Bats have been increasingly studied in the last 15 years in Mato Grosso do Sul, and several records were not yet considered in reviews of South American bat distributions. Here, we present the bat species and their distributions in Mato Grosso do Sul based mainly on data compilation from literature, but also on complementary information from zoological collections, and our and colleagues’ unpublished records. We found 74 species of bats within 42 genera and seven families already reported in Mato Grosso do Sul. Bat species in this state represent 44% of the Brazilian’s bat species (≅ 169) and 7% of the world’s bat richness (≅ 1120). Phyllostomidae (42) and Molossidae (17) were the richest families. Four species formerly cited for Mato Grosso do Sul are not supported by our compilation, and other 15 species recorded in the vicinity are listed as potential occurrences in this state. We additionally found controversial traits for specimens of Platyrrhinus helleri, and report Eumops dabbenei for the first time in Brazil. Most species were recorded in the regions of Cerrado (60) or Pantanal (57) in Mato Grosso do Sul, but only 16 in the Atlantic Forest. Records of Phyllostomidae species were mostly found in Cerrado and those of Molossidae, in Pantanal. Records in Mato Grosso do Sul determine edges of distribution for at least 22 species of South American bats. The overall known chiropteran fauna of Mato Grosso do Sul is highly diverse and new findings are expected through additional surveys.